(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Governmentof India in 1956, brought together over 240 private life insurers and provident societies under one nationalized monopoly corporation and Life Insurance Corporation (LIC)was born. Nationalization was justified on the grounds that it would createmuch-needed funds for rapid industrialization. This was in conformity with theGovernment’s chosen path of State lead planning and development.